Organic and physical chemistry of polymers - Gnanou, Yves (Wiley-Interscience, 2008)
This book provides a thorough introduction to the fundamentals of polymer science, including their structure and synthesis as well as their chemical and physical properties. Covering a wide spectrum of modern polymer science, the book discusses such topic.